Three-Dimensional Electrical Impedance Imaging During Spontaneous Breathing Trials in Patients With Acute Hypoxic Respiratory Failure: A Pilot Study - Nilton Barbosa da Rosa, Jr, MS; Tzu-Jen Kao, MD, PhD; John Brinton, PhD; Patrick J. Offner; Ellen L. Burnham, MD; Jennifer L. Mueller, PhD (Critical Care Explorations)
The purpose of this work is to evaluate the feasibility of lung imaging using 3D electrical impedance tomography (EIT) during spontaneous breathing trials (SBTs) in patients with acute hypoxic respiratory failure. EIT is a noninvasive, nonionizing, real-time functional imaging technique, suitable for bedside monitoring in critically ill patients. EIT data were collected in 24 mechanically ventilated patients immediately preceding and during a SBT on two rows of 16 electrodes using a simultaneous multicurrent source EIT system for 3D imaging. Dynamic 3D EIT images of conductivity were computed, as well as the EIT-derived rapid shallow breathing index, regional ventilation delay, global inhomogeneity index, and time traces of tidal volumes. 3D reconstructions and derived measures demonstrated inhomogeneity in ventilation distribution within patients. We conclude that 3D EIT images can provide information regarding ventilatory heterogeneity across the lung and may be useful in guiding ventilator management.